1995
DOI: 10.1046/j.1471-4159.1995.65062387.x
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Cloning of α1d‐Adrenergic Receptor and Tissue Distribution of Three α1‐Adrenergic Receptor Subtypes in Mouse

Abstract: A partial cDNA encoding most of the third intracellular loop of the mouse a, d -adrenergic receptor subtype was amplified from hippocampus by reverse transcription-polymerase chain reaction (RT-PCR) using degenerate oligodeoxynucleotide primers . This DNA fragment was used as a probe to isolate an a, d -adrenergic receptor cDNA from a mouse brain cDNA library . The deduced amino acid sequence encodes a potential protein of 562 amino acids, and northern hybridization of poly(A)+ RNA isolated from mouse brain de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
14
0

Year Published

1996
1996
2015
2015

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(15 citation statements)
references
References 15 publications
1
14
0
Order By: Relevance
“…However, other recent studies utilizing double ␣ 1A -/␣ 1B -AR knockout mice have revealed the presence of functional ␣ 1D -AR, even in the absence of other ␣ 1 -AR subtypes (Turnbull et al, 2003). Additionally, ␣ 1D -AR is found in some tissues that lack ␣ 1B -AR expression such as human bladder and specific regions of the spinal cord and brain, as well as certain rat and human blood vessels (Alonso-Llamazares et al, 1995;Michelotti et al, 2000;Tanoue et al, 2002;Sadalge et al, 2003). Thus, it is reasonable to speculate that trafficking of functional ␣ 1D -AR to the cell surface may involve the interaction of ␣ 1D -AR with other proteins beyond ␣ 1B -AR.…”
mentioning
confidence: 95%
“…However, other recent studies utilizing double ␣ 1A -/␣ 1B -AR knockout mice have revealed the presence of functional ␣ 1D -AR, even in the absence of other ␣ 1 -AR subtypes (Turnbull et al, 2003). Additionally, ␣ 1D -AR is found in some tissues that lack ␣ 1B -AR expression such as human bladder and specific regions of the spinal cord and brain, as well as certain rat and human blood vessels (Alonso-Llamazares et al, 1995;Michelotti et al, 2000;Tanoue et al, 2002;Sadalge et al, 2003). Thus, it is reasonable to speculate that trafficking of functional ␣ 1D -AR to the cell surface may involve the interaction of ␣ 1D -AR with other proteins beyond ␣ 1B -AR.…”
mentioning
confidence: 95%
“…The primers for the α 1D -AR gene were located within the first exon, and the forward primer was within the region replaced with the Neo in the mutant allele. The primers were derived from the murine α 1A (25), α 1B (25), and α 1D (19,25) sequences. The GAPDH primers (5′→3′) were GGTCATCATCTCCGCCCCTTC upstream and CCACCAC-CCTGTTGCTGTAG downstream (662 bp).…”
Section: Introductionmentioning
confidence: 99%
“…The specificity of the amplified DNA fragments was determined by Southern blot analysis using receptor-specific 32 P-labeled probes (cDNAs of the murine α 1A -AR, α 1B -AR, and α 1D -AR; ref. 25).…”
Section: Introductionmentioning
confidence: 99%